2020
DOI: 10.1101/2020.12.16.20248350
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Extraction-free protocol combining Proteinase K and heat inactivation for detection of SARS-CoV-2 by RT-qPCR

Abstract: Real-time reverse transcription PCR (RT-qPCR) is the gold-standard technique for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) detection in nasopharyngeal swabs specimens. The analysis by RT-qPCR usually requires a previous extraction step to obtain the purified viral RNA. Unfortunately, RNA extraction constitutes a bottleneck for early detection in many countries since it is expensive, time-consuming and depends on the availability of commercial kits. Here, we describe an extraction-free protoc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 30 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…Another possibility would be the use of proteinase K (PK) in the CHUQ protocol. Indeed, some studies suggested that pretreatment of samples with PK increased the sensitivity of direct rRT‐PCR for SARS‐CoV‐2 detection, 28,29 particularly in low positive samples with high C t values 13 . It has been suggested that PK could degrade or inactivate RNAses, allowing to purify a better quality of RNA 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Another possibility would be the use of proteinase K (PK) in the CHUQ protocol. Indeed, some studies suggested that pretreatment of samples with PK increased the sensitivity of direct rRT‐PCR for SARS‐CoV‐2 detection, 28,29 particularly in low positive samples with high C t values 13 . It has been suggested that PK could degrade or inactivate RNAses, allowing to purify a better quality of RNA 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Several methods used combinations of treatments for releasing viral RNA into the reaction for various types of samples. For example, either enzymatic or combination of enzymatic and heat denaturation have been used for Saliva, Sputum, and NP swab samples [ 11 , 12 , 13 , 15 , 16 , 17 , 29 ]. Our data showed that heat denaturation for 2 min alone is sufficient for detecting viral RNA into the sample with no significant loss of PPA when compared to CDC assay ( Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several extraction-free methods were proposed for SARS-CoV-2 testing from various specimen types, such as NP swabs, saliva, and sputum [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. These methods use a combination of enzymatic digestion with heat treatment for sample preparation before RT-qPCR.…”
Section: Introductionmentioning
confidence: 99%
“…For sample processing, a proteinase K-heat inactivation protocol (PK-HID) was applied to samples from swabs stored in viral transport medium (Gibco ® ) [37]. Thus, 95 µl aliquots of samples were treated for 15 minutes at 55 o C with 5 µl of proteinase K (10 mg/ml, stock) prepared at 1 mg/ml in 100 µl of final volume and heat-inactivated at 98 o C for 5 minutes.…”
Section: Sample Processingmentioning
confidence: 99%